(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The Nigerian National Building Code (NBC) offers comprehensive, centralized regulations to guide construction, ensure structural integrity, and promote sustainability. This study investigates the level of implementation of the NBC within Borno State, evaluating five major barriers identified in the literature for field criticality. Using a mixed methods approach with a purposive, maximum variation sampling technique, 320 building projects were selected to assess compliance with 13 key areas of the NBC, involving 450 respondents comprising developers, contractors, clients, construction professionals, and royal fathers. Data were sourced through structured questionnaires and face-to-face dialogues. Field investigation revealed that the NBC is only partially domesticated in Borno State. Data on the five barriers showed overall reliability (α = 0.888). Based on their Relative Importance Index (RII), the barriers were ranked in descending order of criticality as: Stakeholder Non-Compliance and Cultural Resistance; Economic Factors; Legal and Regulatory Bottleneck; Weak Institutional Capacity; and Corruption and Enforcement Failures. Further Chi-Square analysis revealed a significant difference in compliance levels between public and private building projects. Public projects complied with 83.96% of the NBC provisions, while private projects showed only 16.04% compliance. It is concluded that the Borno State Government has failed to enforce code compliance effectively in private projects, leaving residents vulnerable to unsafe, low-quality, and structurally unstable construction. Recommendations include the full domestication of the NBC and the establishment of an independent, statutory commission to oversee code enforcement, among others.